Kinerja Pemerintahan Kota Bogor dalam Pembangunan Manusia untuk Mengatasi Kemiskinan dan Pengangguran di Kota Bogor Tahun 2022 - Alhilal Yusril Hawari; Utang Suwaryo; Dede Sri Kartini (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2023)
This research is motivated by problems that occurred in Bogor City, there are many unemployment and high level of poverty that happen in 2022,. The drop of human development index in 2020 are being judged to be the most impactful factor that rising the number of unemployment and number of poverty. Bogor government performance being one thing that can be seen to know how the role of government to overcome the problem. Therefore, the purpose of this research is to find out how bogor government work performances to overcome the rise of number unemployment and poverty in Bogor.Â  In this research, descriptive method with qualitative approach was used. Data collection was obtained through formal and informal interview, and documentation. Informants were determined by purposive sampling in order to achieve the real data by interviewing informant that are responsible to the conditions. This Research used Wasistiono government organizations work performances theory to measure government work performances through some dimensional such as productivity, service quality, responsivity and resposibility. The researcher can conclude that Bogor government work performances are displeasing in terms of productivity, service quality, and responsivity to human development problems.